Relationship between email subject lines, purposes lines and the communication context. - Leong, Stephen Wenjie. (2008)
This study investigates the extent to which managerial writers in the business context understand the relationship between email subject lines, purpose lines and the communication context. It also examines the extent to which pedagogy accounts for this relationship.